2000
DOI: 10.1159/000013557
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Antineutrophil Cytoplasmic Antibody Test in Lupus Nephritis

Abstract: To elucidate the prevalence and clinical implications of antineutrophil cytoplasmic antibody (ANCA) in lupus nephritis (LN), we examined ANCA by indirect immunofluorescence and by ELISA against antilactoferrin (anti-LF) and antimyeloperoxidase (anti-MPO) antibody. To discriminate perinuclear ANCA (pANCA) with antinuclear antibody (ANA), all the ANCA-positive sera were tested again after incubating patients’ sera with single-stranded (SS) and double-stranded (ds) DNA. These results were compared with clinicopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 15 publications
4
53
0
Order By: Relevance
“…A minority of SLE patients has been reported to develop ANCA (mainly MPO-ANCAs) but, differently from SVV, the pathogenic role of these autoantibodies in SLE is not clear. Contrasting works have reported the presence 28 or the absence 29,30 of correlation between serum ANCA levels and disease activity in SLE. In a large cohort of SLE patients, serum ANCA levels were found to be correlated with specific clinical manifestations, such as serositis, livedo reticularis, and arthritis.…”
Section: Correlation Between Anca Vasculitis and Spontaneous Netosimentioning
confidence: 89%
“…A minority of SLE patients has been reported to develop ANCA (mainly MPO-ANCAs) but, differently from SVV, the pathogenic role of these autoantibodies in SLE is not clear. Contrasting works have reported the presence 28 or the absence 29,30 of correlation between serum ANCA levels and disease activity in SLE. In a large cohort of SLE patients, serum ANCA levels were found to be correlated with specific clinical manifestations, such as serositis, livedo reticularis, and arthritis.…”
Section: Correlation Between Anca Vasculitis and Spontaneous Netosimentioning
confidence: 89%
“…The target antigen by ELISA was LF-ANCA in 25% of patients and MPO-ANCA in 2%. ANCA seropositivity was associated with the presence of nephritis, particularly LN IV, as well as anti-dsDNA antibodies (17). Other reports have failed to show a correlation between ANCA and clinical features or organ involvement (14,18,19).…”
Section: Discussionmentioning
confidence: 87%
“…Some reports show no correlation between organ involvement and the presence of MPO-ANCA [6,7]. On the other hand, it has been reported that MPO-ANCA positivity is associated with specific clinical manifestations of SLE such as serositis [8] and nephritis, particularly lupus nephritis class IV [9,10]. Pan et al [11] examined ANCA positivity in new-onset SLE and reported that ANCApositive lupus patients had a higher incidence of nephritis as well as myocarditis, nerves system disorder and serositis.…”
Section: Discussionmentioning
confidence: 99%